People's practices : exploring contestation, counter-development, and rural livelihoods - Huq, Hamidul, 1955-; Community Development Library (Dhaka, Bangladesh) (Dhaka : Community Development Library, 2001)
With special reference to women in Muktinagar, Bangladesh.
Includes bibliographical references (p. 215-228).
Keywords: Rural development -- Bangladesh -- Muktinagar; Women in rural development -- Bangladesh -- Muktinagar; Rural poor -- Bangladesh -- Muktinagar